Dialektisch-Behaviorale Therapie (DBT) bei einer Patientin mit artifizieller Störung: Behandler- und Patientenperspektive - Joest, Katharina; Feldmann, Robert Enrico; Bohus, Martin (Psychiatrische Praxis, 2012)
Objective: Presentation of the disorder model and inpatient psychotherapy of a patient with factitious disorder as seen from the therapist’s and patient’s perspective. Method: Case report including the patient’s own notations. Results: The description of her motives by the patient facilitated a concise planning of therapy and its successful progression. Conclusions: The factitious disorder is based on learning experiences and is maintained, among other things, by the care of the medical personnel. Principles and interventions of DBT could successfully be employed.